Pelatihan Pembukuan Bumdes Pringgasela Lestari Dan Pengrajin Tenun Di Dusun Gubuk Daya Desa Pringgasela Kecamatan Pringgasela Kabupaten Lombok Timur - Widia Febriana; Rina Komala; Raden Ayu Ida Aryani; Melati Rosanensi; Defel Septian; Wira Hendri (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Historically, the Indonesian nation departed from the diversity of its rich cultural heritage. One of Indonesia's cultural heritage, namely the diversity of traditional woven fabrics. Each region certainly has its own variety of motifs and meanings regarding traditional woven fabric crafts, for example traditional woven crafts on the island of Lombok. One of the producers of woven fabrics on the island of Lombok is the Dusun Gubuk Daya, Pringgasela Village, which is one of the villages in East Lombok Regency. Pringgasela woven fabric has its own characteristics, namely having striped and elongated motifs. One woven fabric can spend three months working from the process of preparing the material to finishing. This weaving activity is one of the livelihoods of women in Pringgasela. Pringgasela woven fabrics come in various lengths with a width of up to 4 meters. To produce this woven cloth, it takes 2 weeks to three months, depending on the diligence of the craftsmen because it is related to the preparatory process before weaving, such as designing motifs, dyeing threads, weaving threads until the sustainability process. sustainability) carried out by weavers. Besides that, the administration is still done manually by the weavers because the weavers do not understand how to book and record finances, the archives are not well organized, and payments are still being made door to door. The abdimas team provides training on simple bookkeeping and simple filing. This research methodology uses a descriptive qualitative approach. This community service data collection method uses interviews, observation and documentation. This interview and observation technique was chosen to gather information about the process of making Sesek Weaving and supported by documentary data in the form of photos of the process of making Sesek Weaving and the data collection process needed to support this research. The results felt by the weavers and Bumdes administrators after carrying out this training were being able to make financial records with a simple financial notebook, there was a consumer filing book to record payments and monthly fees for weaving groups that were gathered in the BUMDes of Pringgasela Village and several people had made payments through the counter.